Foreign Aid and Democratic Stability in Nigeria - Emmanuel Ediba; Abdulaziz Shuaibu Waziri; Emmanuel Achus Jah (Darul Yasin Al Sys, 2026)
Although foreign aid has been widely used to support democratic processes in developing countries, its contribution to long-term democratic stability remains contested. This study examined the impact of foreign aid funding on democratic stability in Nigeria, with particular focus on the 2015 general election, which marked the country’s first successful transfer of power between rival political parties. The study adopted a descriptive research design involving key stakeholders in Nigeria’s electoral process, including officials of the Independent National Electoral Commission, civil society organizations, political parties, and donor agencies. A purposive sample of 15 respondents was selected, and data were collected through key informant interviews and analyzed thematically. The findings revealed that foreign aid funding significantly improved electoral administration, enhanced transparency, strengthened voter education, supported election monitoring, and reduced electoral violence, thereby contributing to democratic stability. However, the study also found that excessive dependence on foreign aid may weaken domestic ownership and limit long-term institutional sustainability. The study concludes that although foreign aid played a stabilizing role in Nigeria’s 2015 general election, sustainable democratic stability requires stronger domestic financing, institutional capacity building, and continuous civic engagement. These findings contribute to debates on democracy assistance by highlighting both the short-term benefits and the structural limitations of foreign aid in democratic consolidation.